CLINICAL AND HEMODYNAMIC PROFILE AND NEUROHORMONAL INDICATORS IN PATIENTS WITH IDIOPATHIC PULMONARY HYPERTENSION, DEPENDING ON VASOREACTIVITY RESERVE OF PULMONARY ARTERIES - V. M. Paramonov; T. V. Martynyuk; Z. H. Dadacheva; N. M. Danilov; V. P. Masenko; I. Ye. Chazova (Евразийский Кардиологический Журнал)
Clinical and hemodynamic profile and neurohormonal indicators in patients with idiopathic pulmonary hypertension, depending on vasoreactivity reserve of pulmonary arteries. Objective: the main objective of our research work was an evaluation of clinical and hemodynamic profile, neurohormonal indicators in patients with IPH, depending on the results of vasoreactivity testing. Methods: the study included 131 patients with IPH (mean age 32,4±3,2 years. All the patients underwent the routine laboratory tests, 6-minuts walking test (6-MWT), transthoracic echocardiography, thorax organs radiography, right heart catheterization (RHC) with acute pharmacological test (APT) using one or two vasodilators (VD) In order to study neurohumoral status the analysis of the 6-keto-PgF1β, NO, ET-1, norepinephrine, epinephrine levels, NT-proANP, NT-proBNP (NUP), renin activity, AII, aldosterone (RAAS) activity was conducted. Results: significant differences of clinical and hemodynamic profile and neurohormonal indicators in patients with IPH depending on the availability (APT +) and absence (APT-) of the vasoreactivity reserve of pulmonary arteries (PA) were established. Among the APT- patients the number of patients belonging to FC III was significantly greater in comparison with APT+ patients. FC IV refered only to the APT- patients. Significantly more patients with APT+ belonged to FC I and II. The 6-MWT revealed that patients with IPH with intact vasodilation reserve overcame significantly longer distance. Doppler echocardiography showed that in APT-group a greater level of systolic pressure in the pulmonary artery (SPPA). When comparing the RHDC data all the hemodynamic parameters in the groups varied considerably, prognostically better data marked APT+ group. According to thorax organs radiography APT- group had significantly higher leel of KTI. Comparative evaluation of neurohumoral status, regardless of the outcome of the APT, showed a significant difference in the groups. Conclusion: the group of responders in comparison with the APT- patients group indicated more safe clinical-hemodynamic and functional status, and neurohumoral rates in the responders group were closer to the outcome in the control group.